Peasant and proletarian : the working class of Moscow in the late nineteenth century - Johnson, Robert Eugene (Leicester : Leicester University Press, 1979)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: 1880-1900.; Moskou